Formulation Development and in vitro Release Kinetics of Divalproex Sodium Sustained Release Matrix Tablet - Biswas, S.K.; Mandal, U.; Pal, T.K. (Asian Journal of Chemistry, 2010)
Divalproex sodium sustained release (SR) matrix tablet has been prepared with different polymers like HPMC K15M, ethyl cellulose, sodium CMC. When the polymer content in the formulation increases, the rate of release becomes more controlled and achieves the desirable limit. The same pattern has been observed incase of all three polymers. No significant difference has been observed between HPMC K15M and sodium CMC towards it's dissolution pattern. The weights, hardness, thickness, percentage friability of the matrix tablets have been found to be identical. It is further observed that inter and intra granulation does not make much variation in release profiles of matrix tablets. The different kinetic models like zero order, first order, Higuchi have been computed with experimental results and the release kinetics largely corroborate the good fitting obtained with Higuichi's model.